Recurrent PTPN14 Mutations in Trichilemmoma: Evidence for Distinct Pathways of Molecular Pathogenesis. (2nd August 2022) - Russell-Goldman, Eleanor; Dong, Fei; Hanna, John
Abstract: Trichilemmoma is a benign cutaneous neoplasm that recapitulates the outer root sheath of the hair follicle. Trichilemmomas may occur sporadically or in association with Cowden syndrome, which is characterized by germline mutations in the lipid phosphatase PTEN (phosphatase and tensin homolog on chromosome 10). Interestingly, most sporadic trichilemmomas do not show PTEN aberrations, but rather activating mutations in HRAS . Despite these important advances, a comprehensive genetic analysis of trichilemmoma has not been reported. Here, we used a next-generation DNA sequencing platform to study 9 sporadic trichilemmoma cases. Seven cases (7/9; 78%) harbored activating mutations in HRAS, consistent with previous findings. Unexpectedly, we identified recurrent mutations in the tyrosine phosphatase PTPN14 (protein tyrosine phosphatase nonreceptor type 14) in 4 cases (4/9; 44%). Three of these cases also harbored HRAS mutations, whereas one case occurred in the absence of a HRAS mutation and showed evidence of biallelic inactivation of PTPN14 . Finally, one case (1/9; 11%) showed biallelic inactivation of PTEN in the absence of a HRAS (or PTPN14 ) mutation. These data suggest at least 3 distinct pathways of molecular pathogenesis in sporadic trichilemmoma and identify PTPN14 as a potentially important contributor to trichilemmoma biology.